Characterization of Binary Organogels Based on Some Azobenzene Compounds and Alkyloxybenzoic Acids with Different Chain Lengths - Yongmei Hu; Qingshan Li; Wei Hong; Tifeng Jiao; Guangzhong Xing; Qilong Jiang (Journal of Spectroscopy)
In this work the gelation behaviors of binary organogels composed of azobenzene amino derivatives and alkyloxybenzoic acids with different lengths of alkyl chains in various organic solvents were investigated and characterized. The corresponding gelation behaviors in 20 solvents were characterized and shown as new binary organic systems. It showed that the lengths of substituent alkyl chains in compounds have played an important role in the gelation formation of gelator mixtures in present tested organic solvents. Longer methylene chains in molecular skeletons in these gelators seem more suitable for the gelation of present solvents. Morphological characterization showed that these gelator molecules have the tendency to self-assemble into various aggregates from lamella, wrinkle, and belt to dot with change of solvents and gelator mixtures. Spectral characterization demonstrated different H-bond formation and hydrophobic force existing in gels, depending on different substituent chains in molecular skeletons. Meanwhile, these organogels can self-assemble to form monomolecular or multilayer nanostructures owing to the different lengths of due to alkyl substituent chains. Possible assembly modes for present xerogels were proposed. The present investigation is perspective to provide new clues for the design of new nanomaterials and functional textile materials with special microstructures.